Endometriosis impact on the course of pregnancy and obstetric outcomes - L.A. Zhabitska; L.A. Zhabitska (Publishing House TRILIST, 2021)
Today, the issues of the pregnancy course in women with endometriosis and endometriosis impact on obstetric outcome remain unresolved and insufficiently studied. Research objective: to study the association between endometriosis and pregnancy complications, adverse obstetric outcomes. Materials and methods. A retrospective cohort study comparing the incidence of pregnancy complications and adverse obstetric outcomes in 478 women with endometriosis (main group) and 544 women without endometriosis (control group). Complications of pregnancy and unfavorable obstetric outcomes were assessed, such as spontaneous miscarriage, ectopic pregnancy, vomiting of pregnant women, premature birth, caesarean section, pathological attachment of the placenta, postpartum hemorrhage and small for gestational age fetuses. Results. The study showed that pregnant women with endometriosis have an increased risk of spontaneous miscarriages compared to the control group: 89/478 (19.07 ± 1.13%) versus 87/544 (14.93 ± 0.49%) respectively (p < 0.001), ectopic pregnancy: 12/478 (2.84 ± 0.47%) versus 5/544 (0.97 ± 0.36%) respectively (p < 0.001); vomiting of pregnant women: 86/478 (17.85 ± 1.09%) compared with 16/544 (3.15 ± 0.34%) respectively (p < 0.001); premature birth: 72/478 (15.5 ± 1.03%) versus 55/544 (10.17 ± 0.30%) respectively (p < 0.001); increased frequency of caesarean section: 99/478 (20.44 ± 1.24%) versus 87/544 (15.5 ± 0.73%) respectively (p < 0.001) and pathological attachment of the placenta: 19/478 (4.31 ± 0.59%) versus 8/544 (1.46 ± 0.30%) respectively (p < 0.001). There was no association between endometriosis and postpartum hemorrhage and small gestational age of the fetus. Conclusions. Pregnant women with endometriosis have an increased risk of spontaneous miscarriages, ectopic pregnancy, vomiting of pregnant women, premature birth, caesarean section, pathological attachment of the placenta. The association established in our study between endometriosis and complications of pregnancy, unfavorable obstetric results requires further research to clarify the mechanisms of the results obtained.